Seks-zabawa w gimnazjum. Znaczenie ulotnych relacji - Przybył, Iwona (Człowiek i Społeczeństwo, 2012)
The author of the based on literature article attempts to characterise various factors that influence sexual activity named “sexual games” among youth. The aim of this paper concentrates on the presentation of the process of constructing identity in a culture of individualism. Characteristic of the postmodern era disintegration of categorical communities, uprooting from tradition and emancipation from social groups and communities results in the emergence of a new man and a new model of socialization. Dynamic socio-cultural changes taking place in Poland cause transformations of intrafamilial and peer relationships that involve a significant weakening of the original compounds in groups and result to identify youth with social networks and weak ties, even in such intimate sphere, which is sex. Secondly, the article tries to present the role and the consequences of this activity.